Cash or Care? Insights from the German Long-Term Care System - Iris Kesternich; André Romahn; Johannes Van Biesebroeck; Marjolein Van Damme (CESifo GmbH, 2025)
The German universal long-term care (LTC) insurance program offers beneficiaries the choice between in-kind services and a cash benefit, which can be used for anything, including informal care. The optimal level of the cash benefit depends on substitution between formal and informal care options, the cost of public funds, and distributional considerations. To evaluate various policy options, we estimate a random-coefficients demand model for the period 1999-2015 using data on the universe of LTC patients supplemented with micro moments from the German Mikrozensus. Results show strong heterogeneity in patient preferences for the three different LTC options: informal, ambulatory and stationary care. A counterfactual analysis predicts that abolishing the cash subsidy leads to a decline in patient surplus that far outweighs the savings in public expenditure. It suggests that manycountries could benefit from the introduction of a cash subsidy option for LTC.
Keywords: I11; G14; L1; 330; aging; long-term care; insurance; informal care